2005
DOI: 10.1111/j.1540-5414.2005.00077.x
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Impact of Interorganizational Systems on Process Efficiency and Sourcing Leverage in Buyer–Supplier Dyads

Abstract: Manufacturing firms are increasingly seeking cost and other competitive advantages by tightly coupling and managing their relationship with suppliers. Among other mechanisms, interorganizational systems (IOS) that facilitate boundary-spanning activities of a firm enable them to effectively manage different types of buyer-supplier relationships. This study integrates literature from the operations and information systems fields to create a joint perspective in understanding the linkages between the nature of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
245
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 309 publications
(256 citation statements)
references
References 63 publications
9
245
1
1
Order By: Relevance
“…However, electronic sourcing is in general increasing process efficiency (Saeed et al, 2005), the collaboration with suppliers (Saeed et al, 2005), price reductions through auction (Arnold et al, 2005), but companies remain concerned about security issues in adapting electronic sourcing (Hartley et al, 2006) or operational risks (Sharp, 2007). Where Emiliani (2004) argues that auctions do not offer real benefits and reduce total costs, Arnold et al (2005) argue the contrary.…”
Section: Electronic Sourcing and Auctionsmentioning
confidence: 99%
See 3 more Smart Citations
“…However, electronic sourcing is in general increasing process efficiency (Saeed et al, 2005), the collaboration with suppliers (Saeed et al, 2005), price reductions through auction (Arnold et al, 2005), but companies remain concerned about security issues in adapting electronic sourcing (Hartley et al, 2006) or operational risks (Sharp, 2007). Where Emiliani (2004) argues that auctions do not offer real benefits and reduce total costs, Arnold et al (2005) argue the contrary.…”
Section: Electronic Sourcing and Auctionsmentioning
confidence: 99%
“…Gelderman and Van Weele (2003) identify in case study research different applications and company-specific characteristics of the Kraljic matrix, particularly where the experienced user included additional informa-tion, such as the overall business strategy, specific situations of supply markets and individual suppliers (Gelderman and Van Weele, 2003). It is surprising that the application of eSourcing or reverse auction is not well established because it improves process efficiencies (Saeed et al, 2005). Research by Spekman et al (1999) identified that, in general, companies lag behind in the implementation of electronic data interchange or other electronic sourcing tools.…”
Section: Tools and Methods Applied For Strategic Sourcingmentioning
confidence: 99%
See 2 more Smart Citations
“…Saeed, Malhotra [34] points out that inter-organizational systems (e.g., e-procurement systems) facilitate the exchange and the process of the information; therefore, the time information substitute the old manual functions. Moreover; e-procurement systems facilitate the execution of complex orders, Brandon-Jones and Carey [33] claimed that user perception of complex order processing quality can be experienced by system speed, accuracy, and capability.…”
Section: Factors Influencing User Satisfactionmentioning
confidence: 99%